JAGR: An Autonomous Self-Recovering Application Server - Candea, George; Kiciman, Emre; Zhang, Steve; Keyani, Pedram; Fox, Armando (The 5th International Workshop on Active Middleware Services, 2003)
This paper demonstrates that the dependability of generic, evolving J2EE applications can be enhanced through a combination of a few recovery-oriented techniques. Our goal is to reduce downtime by automatically and efficiently recovering from a broad class of transient software failures without having to modify applications. We describe here the integration of three new techniques into JBoss, an open-source J2EE application server. The resulting system is JAGR—JBoss with Application-Generic Recovery—a self-recovering execution platform. JAGR combines application-generic failure-path inference (AFPI), path-based failure detection, and micro-reboots. AFPI uses controlled fault injection and observation to infer paths that faults follow through a J2EE application. Path-based failure detection uses tagging of client requests and statistical analysis to identify anomalous component behavior. Micro-reboots are fast reboots we perform at the sub-application level to recover components from transient failures; by selectively rebooting only those components that are necessary to repair the failure, we reduce recovery time. These techniques are designed to be autonomous and application-generic, making them well-suited to the rapidly changing software of Internet services.